Multiple hybridized resonances of IR-806 chromonic molecules strongly coupled to Au nanorods1. Issue 18 (14th May 2015) - Zhang, Ya-Fang; Yang, Da-Jie; Wang, Jia-Hong; Wang, Ya-Lan; Ding, Si-Jing; Zhou, Li; Hao, Zhong-Hua; Wang, Qu-Quan
<x xml:space="preserve">Abstract</x> AuNR@IR-806 hybrids have been prepared using electrostatic interactions, the strong plasmon–molecule coupling of which results in complex dispersion curves.